A Case Report on Juvenile Neuromyelitis Optica: Early Onset, Long Remission Period, and Atypical Treatment Response - Elpers, Christiane; Gross, Catharina C.; Fiedler, Barbara; Meuth, Sven G.; Kurlemann, Gerhard (Neuropediatrics, 2015)
Neuromyelitis optica (NMO) is a severe inflammatory demyelinating disease of the central nervous system and preferentially targets the optic nerves and spinal cord. NMO is rare in children and clinical course of the disease is highly variable as described in studies. Here, we present a case report of a young girl presenting with a rare course of pediatric NMO with an early disease onset at the age of 12 years, a relapse free interval of 4 years, evidence of NMO immunoglobulin G (IgG) and an unusual response against immunosuppressive therapy. The aim of this report is to highlight the potentially long remission period between relapses complicating proper diagnosis despite well defined diagnostic criteria. In addition, we want to encourage the use of rituximab in pediatric NMO, although larger cohorts are warranted to establish B cell depleting therapies in juvenile NMO.
Keywords: neuromyelitis optica; aquaporin 4 (NMO–IgG); rituximab